An Energy-Aware Clustering Protocol Based Grid For WSN - Yousif Khalid Yousid; R Badlishah; N. Yaakob; A Amir (Politeknik Negeri Padang, 2018)
One of the most critical problems in Wireless Sensor Networks (WSNs) is to how to reduce energy consumption and prolong the network lifetime of WSNs. Clustering is of the solutions, which have been used to reduce energy consumption by partition the network into clusters. However; most of the clustering schemes select the cluster head (CH) either randomly or based on centralized manner. Both approaches lead to deficient utilization of WSN resources. Therefore, the purpose of this paper is to illustrate a new multi-hop clustering protocol called EACPG, which aimed to provide energy efficiency and maintain load balancing. In EACPG the network is divvied into multiple numbers of virtual square grids. Also, different parameters are considered for cluster head election based on distributed manner. In addition, a new mechanism for CH rotation is used in order to maintain load balancing between CHs. Finally, Results show that the proposed scheme has better performance in term of energy consumption and the number of alive sensor nodes and throughput.